Kinerja Keuangan Perusahaan Pada Harga Saham Perusahaan Food and Beverage di Indonesia - Ainul, Nazilatul Khunaina Il Khafa; Wulandari, Annisa (E-Jurnal Akuntansi, 2022)
The background of the research is the importance of the company's financial performance in making investment decisions for potential investors. The purpose of this study was to determine and analyze the effect of the Current Ratio, Total Asset Turnover, Debt to Equity Ratio, Return on Equit, and Price Earnings Ratio on the Stock Price of Food and Beverage Companies for the 2015-2019 period. The sample in this study used a purposive sampling technique and the final sample was 54 food and beverage companies during the sample period. The analytical tool used is multiple linear regression. The results showed that the Current Ratio, Return on Equity and Price Earnings Ratio had an effect on stock prices. Meanwhile, Total Asset Turnover and Debt to Equity Ratio have no effect on stock prices. Keywords: Current Ratio; Total Asset Turnover; Debt to Equity Ratio; Return on Equity; Price Earnings Ratio; Stock Price.